A review of the African redflanked skinks of the Lygosoma fernandi (BURTON, 1836) species group (Squamata: Scincidae) and the role of climate change in their speciation - Wagner, Philipp; Böhme, Wolfgang; Pauwels, Olivier S. G.; Schmitz, Andreas (Zootaxa, 2009)
We present an analysis of the morphometric and genetic variability of Lygosoma fernandi. Geographical variation and taxonomic consequences are discussed and Lepidothyris Cope, 1892 is resurrected as genus for the L. fernandi species group. The results show that Lepidothyris fernandi sensu lato is a species complex, which comprises an eastern and a western species. Each of them has a further subspecies of its own, and a third distinct species is present in southwestern Central Africa. The morphological and genetic differences between these taxa are analyzed resulting in the description of two new taxa, and the resurrection of two more taxa.